Carbon dioxide exchange of a perennial bioenergy crop cultivation on a mineral soil - S. E. Lind (Biogeosciences, 2016)
One of the strategies to reduce carbon dioxide (CO2) emissions from the energy sector is to increase the use of renewable energy sources such as bioenergy crops. Bioenergy is not necessarily carbon neutral because of greenhouse gas (GHG) emissions during biomass production, field management and transportation. The present study focuses on the cultivation of reed canary grass (RCG, Phalaris arundinacea L.), a perennial bioenergy crop, on a mineral soil. To quantify the CO2 exchange of this RCG cultivation system, and to understand the key factors controlling its CO2 exchange, the net ecosystem CO2 exchange (NEE) was measured from July 2009 until the end of 2011 using the eddy covariance (EC) method. The RCG cultivation thrived well producing yields of 6200 and 6700 kg DW ha−1 in 2010 and 2011, respectively. Gross photosynthesis (GPP) was controlled mainly by radiation from June to September. Vapour pressure deficit (VPD), air temperature or soil moisture did not limit photosynthesis during the growing season. Total ecosystem respiration (TER) increased with soil temperature, green area index and GPP. Annual NEE was −262 and −256 g C m−2 in 2010 and 2011, respectively. Throughout the study period from July 2009 until the end of 2011, cumulative NEE was −575 g C m−2. Carbon balance and its regulatory factors were compared to the published results of a comparison site on drained organic soil cultivated with RCG in the same climate. On this mineral soil site, the RCG had higher capacity to take up CO2 from the atmosphere than on the comparison site.